Electrode active materials for electrochemical elements, electrode materials for electrochemical elements, electrodes for electrochemical elements, electrochemical elements, and mobile bodies

JP7943848B2Active Publication Date: 2026-10-30MAXELL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023505304
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-11
Filing Date
2022-02-28
Publication Date
2026-10-30
Estimated Expiration
2042-02-28

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、負荷特性に優れた電気化学素子、前記電気化学素子を構成し得る電極活物質、電極材料および電極、並びに前記電気化学素子を有する移動体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943848000003
    Figure 0007943848000003
  • Figure 0007943848000004
    Figure 0007943848000004
  • Figure 0007943848000005
    Figure 0007943848000005
Patent Text Reader

Abstract

The present invention provides: an electrochemical element which has excellent load characteristics; an electrode active material, an electrode material and an electrode, each of which is capable of constituting the electrochemical element; and a mobile object which comprises the electrochemical element. An electrode active material for electrochemical elements according to the present invention is characterized by being composed of a monoclinic niobium composite oxide, and is also characterized in that if Da is the crystallite size in the a-axis direction and Db is the crystallite size in the b-axis direction, Db / Da is 1.5 or more. In addition, an electrode material for electrochemical elements according to the present invention is characterized by containing the electrode active material for electrochemical elements according to the present invention; and an electrode for electrochemical elements according to the present invention is characterized by containing the electrode active material for electrochemical elements according to the present invention or the electrode material for electrochemical elements according to the present invention. In addition, an electrochemical element according to the present invention is characterized in that either the positive electrode or the negative electrode thereof is the electrode for electrochemical elements according to the present invention. Meanwhile, a mobile object according to the present invention is characterized by comprising the electrochemical element according to the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an electrochemical element with excellent load characteristics, an electrode active material that can constitute the electrochemical element, an electrode material and an electrode, and a mobile body having the electrochemical element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, a type of electrochemical device, are used as power sources for portable electronic devices such as mobile phones and notebook computers, as well as electric vehicles. However, with the miniaturization and increased functionality of these devices, non-aqueous electrolyte secondary batteries are required to be smaller, lighter, and have higher capacity and energy density.

[0003] In current non-aqueous electrolyte secondary batteries, lithium-containing composite oxides are typically used as the positive electrode active material, and graphite or similar materials are used as the negative electrode active material.

[0004] Furthermore, in order to construct a battery that can be charged and discharged at high current values ​​without causing an internal short circuit due to lithium deposition at the negative electrode, for example, the negative electrode active material is made of spinel-type lithium titanate (Li4Ti5O 12 Attempts have also been made to use ). However, lithium titanate has a theoretical capacity of [175 mAh / g (600 mAh / cm²). 3 )〕 is the theoretical capacity of graphite [372mAh / g (830mAh / cm³] 3 It is smaller than [another product], and therefore faces challenges in this regard.

[0005] For these reasons, in recent years, oxides of niobium and other metals, such as niobium-titanium composite oxides, have been considered as a negative electrode active material with a larger capacity than lithium titanate (Patent Documents 1 and 2, Non-Patent Document 1, etc.).

[0006] Patent Document 1 states that by incorporating specific amounts of Mo, V, or W into a monoclinic niobium-titanium composite oxide, and by keeping the aspect ratio and crystallite size of its primary particles within a specific range, a non-aqueous electrolyte battery with excellent input / output characteristics and cycle characteristics can be realized.

[0007] Furthermore, Patent Document 2 states that the charge-discharge cycle characteristics of a secondary battery can be improved by setting a specific value for the ratio of the crystallite diameter related to the (020) plane to the average primary particle diameter of particles having a crystal structure belonging to monoclinic niobium-titanium composite oxide.

[0008] In niobium composite oxides, the crystallite size related to the (020) plane corresponds to the crystallite size in the b-axis direction. Non-patent document 1 shows that in niobium composite oxides, the diffusion rate of Li ions in the b-axis direction is larger than, for example, the diffusion rate in the a-axis direction. [Prior art documents] [Patent Documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2016-177972 [Patent Document 2] Japanese Patent Publication No. 2019-57371 [Non-patent literature]

[0010] [Non-Patent Document 1] Journal of the American Chemical Society, 2019, Vol. 141, pp. 16706-16725 [Overview of the project] [Problems that the invention aims to solve]

[0011] As mentioned above, niobium composite oxides are less prone to lithium deposition at the negative electrode even when charged and discharged at high current values. Therefore, using them as an active material is expected to improve the load characteristics of electrochemical elements such as non-aqueous electrolyte secondary batteries. However, as the devices that utilize electrochemical elements are expected to develop further in the future, electrochemical elements will require even greater improvements in load characteristics to meet these demands.

[0012] The present invention has been made in view of the above circumstances, and its object is to provide an electrochemical element with excellent load characteristics, an electrode active material that can constitute the electrochemical element, an electrode material and an electrode, and a mobile body having the electrochemical element. [Means for solving the problem]

[0013] The electrode active material for electrochemical elements of the present invention is a monoclinic niobium composite oxide, characterized in that when the crystallite size in the a-axis direction is Da and the crystallite size in the b-axis direction is Db, the ratio Db / Da is 1.5 or greater.

[0014] Furthermore, the electrode material for electrochemical elements of the present invention is characterized by containing the electrode active material for electrochemical elements of the present invention.

[0015] Furthermore, the electrode for the electrochemical element of the present invention is characterized by containing the electrode active material for the electrochemical element of the present invention, or containing the electrode material for the electrochemical element of the present invention.

[0016] Furthermore, the electrochemical element of the present invention has a positive electrode and a negative electrode, and is characterized in that either the positive electrode or the negative electrode is an electrode for the electrochemical element of the present invention.

[0017] Furthermore, the mobile body of the present invention is characterized by having the electrochemical element of the present invention. [Effects of the Invention]

[0018] According to the present invention, it is possible to provide an electrochemical element with excellent load characteristics, an electrode active material that can constitute the electrochemical element, an electrode material and an electrode, and a mobile body having the electrochemical element. [Brief explanation of the drawing]

[0019] [Figure 1] This is a schematic cross-sectional view showing an example of the electrochemical element of the present invention. [Figure 2] This is a schematic plan view illustrating another example of the electrochemical element of the present invention. [Figure 3] This is a cross-sectional view taken along line II in Figure 2. [Figure 4] This graph shows the relationship between the ratio of Da to average particle diameter ("Da / average particle diameter") in the niobium composite oxide used as the negative electrode active material for Examples 1 and 3, and Comparative Examples 1 and 2, and the charging and discharging characteristics of the battery. [Modes for carrying out the invention]

[0020] <Electrode Active Materials for Electrochemical Devices> The electrode active material for the electrochemical element of the present invention (hereinafter sometimes simply referred to as "active material") is a monoclinic niobium composite oxide, wherein the ratio of the crystallite size in the a-axis direction (Da) to the crystallite size in the b-axis direction (Db) is 1.5 or greater.

[0021] As mentioned above, in monoclinic niobium composite oxides, the diffusion rate of Li ions in the b-axis direction is known to be faster than, for example, the diffusion rate in the a-axis direction.

[0022] In typical monoclinic niobium composite oxides, the crystallite size in the a-axis direction is equivalent to the crystallite size in the b-axis direction. However, after extensive research, the inventors discovered that by controlling the manufacturing conditions of the niobium composite oxide, it is possible to make the crystallite size Da in the a-axis direction smaller than the crystallite size Db in the b-axis direction. Furthermore, they found that by adjusting Da and Db in this way to achieve a Db / Da ratio of 1.5 or higher, the capacitance of the electrochemical element can be fully utilized even when charged and discharged at high currents, thereby improving its load characteristics. This led to the completion of the present invention.

[0023] In the monoclinic niobium composite oxide constituting the active material, the Db / Da ratio is preferably 1.5 or higher, more preferably 1.7 or higher, and more preferably 3.0 or higher, from the viewpoint of suppressing the crystallite size in the a-axis direction where the diffusion rate of Li ions is lower, thereby increasing the diffusion rate of Li ions throughout the active material and enabling the construction of an electrochemical element with excellent loading characteristics.

[0024] Furthermore, in the monoclinic niobium composite oxide constituting the active material, if the Db / Da ratio is too high, the crystal structure may become unstable, potentially reducing reversibility during charging and discharging. Therefore, in the monoclinic niobium composite oxide constituting the active material, the Db / Da ratio is preferably 10 or less, and more preferably 7.0 or less.

[0025] Furthermore, in the monoclinic niobium composite oxide constituting the active material, the crystallite size Da in the a-axis direction is preferably 5 nm or larger, more preferably 10 nm or larger, preferably 500 nm or smaller, and more preferably 100 nm or smaller. Moreover, in the monoclinic niobium composite oxide constituting the active material, the crystallite size Db in the b-axis direction is preferably 7.5 nm or larger, more preferably 15 nm or larger, preferably 5000 nm or smaller, and more preferably 1000 nm or smaller.

[0026] Examples of monoclinic niobium composite oxides constituting the active material include those having a ReO3 type crystal structure and containing a crystalline phase belonging to the space group I2 / m having a 3×4×∞ block structure in the crystallographic shear structure (C2 / m, A2 / m) or a 3×3×∞ block structure. Preferably, examples include those having a ReO3 type crystal structure and containing a crystalline phase belonging to the space group having a 3×4×∞ block structure in the crystallographic shear structure.

[0027] Examples of niobium composite oxides constituting the active material of the present invention include composite oxides represented by the following general formula (1) (niobium aluminum composite oxide).

[0028] M x Al 1-1.5x Nb 11+0.5x O 29-δ (1)

[0029] In the general formula (1) above, M is at least one element from Zn and Cu, and 0 ≤ x ≤ 0.4 and 0 ≤ δ ≤ 3.

[0030] In other words, the composite oxide satisfying the general formula (1) does not have to contain element M, and may contain at least one of Zn and Cu, which are element M. When the composite oxide represented by the general formula (1) contains element M, its amount x is preferably 0.05 or more, as this further improves the effect of enhancing the load characteristics of the electrochemical element. However, if the amount of element M in the composite oxide represented by the general formula (1) is too high, the stability of the crystal structure may decrease, which may reduce the charge-discharge cycle characteristics of the electrochemical element. Therefore, from the viewpoint of improving the charge-discharge cycle characteristics of the electrochemical element, the amount x of element M in the composite oxide represented by the general formula (1) is preferably 0.4 or less, and more preferably 0.35 or less.

[0031] In the composite oxide represented by the aforementioned general formula (1), δ relating to the amount of oxygen is determined according to the valences of element M and Nb, such that the total amount (valence) of element M, Nb and Al that form cations matches the total amount (valence) of oxygen that forms anions. Specifically, the value of δ is 0 or more and 3 or less.

[0032] Incidentally, in the composite oxide represented by the aforementioned general formula (1), the coexistence of pentavalent Nb and tetravalent Nb may cause oxygen defects (that is, δ may become greater than 0 in the aforementioned general formula (1)). For example, when Cu is contained as element M, although the reason is not clearly known, it has been found that the effect of enhancing the load characteristics of the electrochemical element is further improved.

[0033] Further, as the niobium composite oxide constituting the active material, TiNb2O7 and Ti2Nb 10 O 29 other niobium-titanium composite oxides can also be used.

[0034] The niobium composite oxide constituting the active material comes to contain Li as Li ions are inserted, through charging of an electrochemical element in which it is used as a negative electrode active material, or through pre-doping of Li ions before it is used in an electrochemical element. For example, in the case of the niobium composite oxide represented by the aforementioned general formula (1), insertion of Li ions leads to satisfaction of, for example, the following general formula (2).

[0035] Li y M x Al 1-1.5x Nb 11+0.5x O 29-δ (2)

[0036] In the aforementioned general formula (2), element M, its amount x, and δ relating to the amount of oxygen are the same as in the aforementioned general formula (1), and y ≤ 22.

[0037] As previously described, the composition of the active material of the present invention can be represented, for example, by the general formula (1) or (2). However, the niobium composite oxide constituting the active material may contain typical elements such as Na, K, Mg, Ca, C, S, P, and Si, as well as transition elements such as Ti, Zr, Fe, Cr, Ni, Mn, Ta, Y, Cu, and Zn. It may also be composed of at least one element selected from the above elements and Nb, without containing Al. Furthermore, the niobium composite oxide constituting the active material may contain water.

[0038] Because the active material of the present invention exhibits excellent output, it is less susceptible to the effects of polarization caused by Li ion diffusion within the active material due to the increased particle size of the active material particles. For the same reason, the primary particles of the active material may form aggregates (secondary particles). However, in the case of secondary particles, it is preferable that the primary particles of the active material are sintered together, and more preferably that they are primary particles, as this improves the load characteristics and charge-discharge cycle characteristics of the electrochemical element.

[0039] Furthermore, the average particle size of the active material is preferably 0.1 μm or larger, more preferably 0.5 μm or larger, from the viewpoint of reducing side reactions that cause capacitance degradation of the electrochemical element and increasing electrode density. Additionally, from the viewpoint of suppressing charge transfer resistance on the surface of the active material particles, it is preferably 25 μm or smaller, and more preferably 10 μm or smaller.

[0040] Since the active material of the present invention has excellent chemical stability, electrolytes such as aqueous solutions, non-aqueous solutions, and solid electrolytes may be used. However, from the viewpoint of maintaining the excellent output characteristics of the active material of the present invention without causing gas generation or the growth of insulating films over a long period of time, it is more preferable to use it together with a solid electrolyte.

[0041] Therefore, the active material of the present invention is preferably used as an active material (positive electrode active material or negative electrode active material) in an electrochemical element having a solid electrolyte (such as an all-solid-state secondary battery). Furthermore, the electrode material for electrochemical elements of the present invention, described later, preferably contains a solid electrolyte together with the active material of the present invention. Moreover, the electrode for electrochemical elements of the present invention preferably contains a solid electrolyte together with the active material of the present invention, or contains an electrode material for electrochemical elements of the present invention that contains a solid electrolyte.

[0042] <Method for manufacturing electrode active materials for electrochemical elements> The method for producing the active material of the present invention is not particularly limited, but for example, it can be synthesized by a solid-phase reaction method in which various metal oxides of Nb, Al, Cu, and Zn are mixed and calcined, or by a reaction method in which a mixture of metal compounds prepared by co-precipitating chloride salts, nitrates, or alkoxides of each metal in a liquid phase is used as a precursor.

[0043] In the solid-phase reaction method, from the viewpoint of enhancing the interdiffusion of various metal ions, it is preferable to calcine at a temperature of 800°C or higher, and more preferably in the range of 900°C to 1100°C. The calcination time is not particularly limited, but can be carried out under conditions of 1 to 1000 hours. If the calcination temperature exceeds 1100°C, oxygen is gradually released from the sample, which can lead to the formation of crystalline phases other than the monoclinic crystalline phase, or the composition may no longer satisfy, for example, the general formulas (1) and (2) above. Therefore, it is more preferable to keep the temperature above 1100°C for no more than 10 hours. The cooling rate of the sample during calcination is not particularly limited as long as a monoclinic crystalline phase can be obtained, but in order to obtain a monoclinic crystalline phase that is stable at the above temperature, a cooling rate of 15°C / min to 60°C / min (including natural cooling) is preferable. Rapid cooling treatment may also be performed at a cooling rate in the range of 1°C / second to 1000°C / second.

[0044] <Method for determining the composition of electrode active materials for electrochemical elements> The composition of the active material of the present invention can be analyzed, for example, using inductively coupled plasma atomic emission spectroscopy (ICP-AES). If quantitative analysis using ICP-AES is difficult due to the active material of the present invention being sintered with an oxide-based solid electrolyte and difficulty in separating each component, the composition can also be determined by combining various elemental analysis methods such as energy-dispersive X-ray spectrometer (EDS) or wavelength-dispersive X-ray spectrometer (WDS) with a scanning electron microscope (SEM) or transmission electron microscope (TEM).

[0045] <Method for confirming oxygen vacancies in electrode active materials for electrochemical elements> The presence of oxygen vacancies in the active material (the niobium complex oxide that constitutes it) can be confirmed by X-ray photoelectron spectroscopy (XPS), which shows a mixture of peaks attributed to pentavalent Nb and peaks attributed to tetravalent Nb in these complex oxides (this method was used in the examples described later). The peak position of C1s in the contaminating hydrocarbons on the sample surface was set to 284.6 eV, and the charge correction of the spectral binding energy was performed to obtain XPS spectra in the binding energy range of 202 eV to 214 eV. The background shape was estimated using the iterative Shirley method, and the background was removed from the spectrum. Peak fitting was performed on the obtained spectrum using the Pseudo-Voigt function, and the Nb of Nb3d3 / 2 was identified. 5+ The area of ​​the peak attributed to (obtained at the binding energy of 209.8 eV to 210.2 eV) and Nb 4+ Peaks attributed to (Nb 5+ The area of ​​the peak (where the binding energy is 0.5eV to 2eV lower than the peak position assigned to 3d3 / 2) is determined, and the average valence of Nb is calculated. Similarly, the area of ​​the Nb of Nb3d5 / 2 is determined. 5+ The area of ​​the peak attributed to (obtained at the binding energy of 206.6 eV to 207.1 eV) and Nb 4+ Peaks attributed to (Nb 5+The area of ​​the peak (where the binding energy is 0.5eV to 2eV lower than the peak attributed to 3d5 / 2) is determined, and the average valence of Nb is calculated. The average value of the average valence of Nb calculated from Nb3d3 / 2 and the average valence of Nb calculated from Nb3d5 / 2 is calculated to determine the average valence of Nb contained in the active material.

[0046] Similar to the average valence of Nb, the average valence of Cu can also be determined. XPS spectra were obtained in the binding energy range of 925 eV to 950 eV, and the Cu of Cu2p3 / 2 was determined. 2+ The area of ​​the peak attributed to (obtained at the bond energy of 932.7eV~934.6eV) and Cu + Peaks attributed to (Cu 2+ The area of ​​the peak (where the bond energy is 0.5eV to 2eV lower than the peak attributed to 2p3 / 2) is determined, and the average valency of Cu is determined.

[0047] Next, the amounts of various metal elements are quantified using Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES). 5 mg of the sample is placed in a platinum crucible, 5 ml of hydrofluoric acid and 10 ml of 50% by mass sulfuric acid are added, and the mixture is heated and decomposed to obtain a mixture of concentrated sulfuric acid and fluoride salts of various metals (at this time, the hydrofluoric acid turns into white fumes and is removed). After adding 2 ml of 30% by mass hydrogen peroxide solution to the obtained mixture, the sample is diluted with pure water to a total volume of 100 ml using a volumetric flask. The obtained sample solution and standard solutions with known concentrations of each metal are measured alternately three times, and the average value is calculated for each. The amount of metal elements in the sample is determined from the ratio of the signal intensity of the sample solution to the signal intensity of the standard solution.

[0048] The average valence of Nb and Cu elements determined by XPS analysis (all Al elements are Al 3+ (Assuming they exist in this state), the total charge of cations contained in the sample is calculated from the content of various metal elements determined by ICP-AES, and oxygen anions (O) are used to make the total charge of the obtained cations electrically neutral. 2-The content of ) is calculated, and the difference between this and the oxygen anion content assuming no oxygen vacancies are present is defined as the oxygen vacancy amount δ. That is, in the case of niobium composite oxides represented by general formula (1), Al, Cu, and Nb in the sample are each Al 3+ and Cu 2+ Nb 5+ The difference between the oxygen content assuming that the system is composed of the above and the oxygen content obtained by the above method is the amount of oxygen deficiency δ.

[0049] Alternatively, the oxygen content in the sample may be directly quantified by placing the sample in a graphite crucible, resistively heating it in a helium stream, and detecting the generated carbon dioxide with an infrared detector.

[0050] <Method for confirming the monoclinic crystal structure of electrode active materials for electrochemical devices> The crystal structure of the active material of the present invention can be determined by measuring the powder X-ray diffraction (powder XRD) pattern using a Rigaku RINT2500VPC (X-rays used: CuKα rays) and comparing it with the Powder Diffraction File (PDF) database, or by analyzing it using the Rietveld method. When comparing crystal lattice sizes between different samples, Si powder (manufactured by Rigaku, a0 = 5.4308 Å at 298.1 K) is mixed as an internal reference during sample preparation for powder XRD measurement, and the spectrum is corrected so that the peak attributed to the X-ray diffraction of the (111) plane of Si becomes 2θ = 28.442 degrees. The lattice constant (d) in the b-axis direction of the unit cell 010The interplanar spacing can be calculated by setting the X-ray wavelength to 1.5418 Å and doubling the interplanar spacing obtained from the peak attributed to the diffraction of the (020) plane. When the active material of the present invention is contained in the negative electrode as a negative electrode active material, the negative electrode of the battery is removed after performing a constant resistance discharge for 100 hours by connecting a 1 kΩ resistor to the battery, and the surface of the electrode opposite to the surface in contact with the current collector is flattened so that it is parallel to the current collector, and then the powder XRD pattern of the electrode can be obtained by fixing it to a sample stage for powder XRD. When the active material of the present invention is contained in the positive electrode as a positive electrode active material, the positive electrode of the battery is removed after performing a constant current charge of 10 μA under the condition of a maximum voltage of 3 V, and then holding it in a constant voltage state of 3 V for 100 hours, and similar to the case of the negative electrode, the surface of the electrode opposite to the surface in contact with the current collector is flattened so that it is parallel to the current collector, and then the powder XRD pattern of the electrode can be obtained by fixing it to a sample stage for powder XRD.

[0051] When the active material of the present invention has a form in which it is sintered with a crystalline sulfide-based solid electrolyte or an oxide-based solid electrolyte, a sample piece can be extracted from a molded body of the sample containing the active material of the present invention using focused ion beam (FIB) processing, mounted on a TEM sample stage, and thinned to a thin film with a thickness of 100 nm or less. The selected area electron diffraction (SAED) pattern can then be obtained using TEM and analyzed to confirm the monoclinic structure.

[0052] <Method for measuring Da and Db in active materials for electrochemical elements> The Da and Db values ​​of the active material (the monoclinic niobium composite oxide that constitutes it) are calculated by determining the full width at half maximum of a specific peak from the powder X-ray diffraction pattern of the active material obtained by the above method, and then using the Scherrer formula described below.

[0053] D = Kλ / wcosθ

[0054] In the above formula, D is the crystallite size, K is the Scherrer constant, λ is the wavelength of the X-ray, w is the full width at half maximum, and θ is the Bragg angle.

[0055] When the space group of the monoclinic niobium composite oxide constituting the active material is assigned to C2 / m, the crystallite size Da in the a-axis direction is determined by the peak of the (200) plane, and the crystallite size Db in the b-axis direction is determined by the peak of the (020) plane. Furthermore, when the space group of the monoclinic niobium composite oxide constituting the active material is assigned to A2 / m, the crystallite size Da in the a-axis direction is determined by the peak of the (400) plane, and the crystallite size Db in the b-axis direction is determined by the peak of the (020) plane. In addition, when the space group of the monoclinic niobium composite oxide constituting the active material is assigned to I2 / m, the crystallite size Da in the a-axis direction is determined by the peak of the (400) plane, and the crystallite size Db in the b-axis direction is determined by the peak of the (020) plane.

[0056] <Method for measuring the average particle size of active materials for electrochemical elements> The average particle diameter of the active material of the present invention is the 50% diameter value in the volume-based integrated fraction when determining the integrated volume from the smallest particles using a particle size distribution analyzer (such as the Microtrac particle size distribution analyzer "HRA9320" manufactured by Nikkiso Co., Ltd.). 50 This means (the same applies to particles such as solid electrolytes and positive electrode active materials, which will be discussed later).

[0057] <Electrode materials for electrochemical elements> The electrode material for electrochemical elements of the present invention (hereinafter sometimes simply referred to as "electrode material") contains the electrode active material for electrochemical elements of the present invention, and together with the active material, it may contain other materials for constituting the electrode for the electrochemical element. Examples of such materials include conductive additives such as carbon black, binders, and solid electrolytes, and the electrode material may contain one or more of these together with the active material of the present invention, as needed.

[0058] The electrode material may have other materials attached to the surface of the active material, or it may be a mixture of the active material and other materials, or it may simply be the presence of both the active material and the other materials.

[0059] When the electrode material contains carbon black, examples of carbon black include thermal black, furnace black, channel black, Ketjen black, and acetylene black. When the electrode material contains carbon black, the carbon black content in the electrode material can be, for example, 0.1 to 25 parts by mass per 100 parts by mass of the active material of the present invention.

[0060] When the electrode material contains a binder, examples of such binders include fluororesins such as polyvinylidene fluoride (PVDF). When the electrode material contains a binder, the binder content in the electrode material can be, for example, 0.1 to 25 parts by mass per 100 parts by mass of the active material of the present invention.

[0061] When the electrode material contains a solid electrolyte, the solid electrolyte is not particularly limited as long as it has Li ion conductivity, and for example, sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, oxide-based solid electrolytes, etc., can be used.

[0062] Examples of sulfide-based solid electrolytes include particles such as Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3 glass, as well as thio-LISICON type electrolytes, which have recently attracted attention for their high Li ion conductivity. 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 such as, 12-12a-b+c+6d-e M 1 3+a-b-c-d M 2 b M 3 c M 4 d M 5 12-e X e (However, M 1 is Si, Ge or Sn, M 2 is P or V, M 3is Al, Ga, Y or Sb, M 4 is Zn, Ca, or Ba, M 5 is either S or S and O, X is F, Cl, Br or I, 0≦a<3, 0≦b+c+d≦3, 0≦e≦3], and argyrodite type ones [such as Li6PS5Cl, Li 7-f+g PS 6-x Cl x+y (provided that 0.05≦f≦0.9, -3.0f+1.8≦g≦-3.0f+5.7), Li 7-h PS 6-h Cl i Br j (provided that h=i+j, 0<h≦1.8, 0.1≦i / j≦10.0), etc.] can also be used.

[0063] Examples of the hydride-based solid electrolyte include LiBH4, solid solutions of LiBH4 and the following alkali metal compounds (for example, those having a molar ratio of LiBH4 to the alkali metal compound of 1:1 to 20:1), and the like. Examples of the alkali metal compound in the solid solution include ha logenated lithium (LiI, LiBr, LiF, LiCl, etc.), halogenated rubidium (RbI, RbBr, RbF, RbCl, etc.), halogenated cesium (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and at least one selected from the group consisting of cesium amide.

[0064] Examples of the halide-based solid electrolyte include monoclinic LiAlCl4, defective spinel-type or layered structure LiInBr4, monoclinic Li 6-3m Y m X6 (provided that 0<m<2 and X=Cl or Br), and the like, and other known ones described in, for example, International Publication No. 2020 / 070958 and International Publication No. 2020 / 070955 can also be used.

[0065] Examples of oxide-based solid electrolytes include Li2O-Al2O3-SiO2-P2O5-TiO2 glass ceramics, Li2O-Al2O3-SiO2-P2O5-GeO2 glass ceramics, and garnet-type Li7La3Zr2O 12 , NASICON type Li 1+O Al 1+O Ti 2-O (PO4)3, Li 1+p Al 1+p Ge 2-p (PO4)3, perovskite-type Li 3q La 2 / 3-q Examples include TiO3.

[0066] Among these solid electrolytes, sulfide-based solid electrolytes are preferred due to their high Li ion conductivity, sulfide-based solid electrolytes containing Li and P are more preferred, and argyrodite-type sulfide-based solid electrolytes, which have high Li ion conductivity and high chemical stability, are even more preferred.

[0067] If the electrode material contains a solid electrolyte, the amount of solid electrolyte in the electrode material can be, for example, 0.1 to 500 parts by mass per 100 parts by mass of the active material of the present invention.

[0068] <Electrodes for electrochemical elements> The electrode for the electrochemical element of the present invention (hereinafter sometimes simply referred to as "electrode") contains the active material or electrode material of the present invention and is used as the positive or negative electrode of an electrochemical element such as a non-aqueous electrolyte secondary battery.

[0069] Examples of electrodes in the present invention include molded bodies (such as pellets) formed by molding an electrode mixture containing an active material and an electrode material, and structures in which a layer (electrode mixture layer) made of a molded electrode mixture is formed on a current collector.

[0070] When using the active material of the present invention, the electrode mixture constituting the electrode may contain the active material along with necessary materials from among conductive additives, binders, solid electrolytes, etc. Similarly, when using the electrode material of the present invention, the electrode mixture constituting the electrode may also contain the electrode material along with necessary materials from among conductive additives, binders, solid electrolytes, etc. However, depending on the component composition of the electrode material, the electrode mixture may be composed solely of the electrode material.

[0071] Examples of conductive additives for electrode mixtures include the various carbon blacks exemplified above that can be used as electrode materials, as well as carbon materials such as graphite (natural graphite, artificial graphite), graphene, vapor-grown carbon fibers, carbon nanofibers, and carbon nanotubes; powders of Cu, Ni, Al, Au, and Pd or their alloys, or porous materials thereof; these may be used individually or in combination of two or more. The content of conductive additives in the electrode mixture (including the amount of carbon black if the electrode material used in the electrode mixture contains carbon black) is preferably 0 to 25% by mass.

[0072] The binder for the electrode mixture can be the same as those previously exemplified for use in electrode materials. However, if good moldability can be ensured in forming a molded body of the electrode mixture without using a binder, for example, when the electrode mixture contains a sulfide-based solid electrolyte and the powder of the electrode mixture is placed in a mold to form a compact (including cases where the electrode material constituting the electrode mixture contains a sulfide-based solid electrolyte), then the electrode material does not need to contain a binder.

[0073] In electrode mixtures, if a binder is required, its content (including the amount of binder if the electrode material used in the electrode mixture contains a binder) is preferably 15% by mass or less, and more preferably 0.5% by mass or more. On the other hand, in electrode mixtures where moldability can be obtained without a binder because a sulfide-based solid electrolyte is included, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0% by mass (i.e., no binder is included).

[0074] The solid electrolyte in the electrode mixture may be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as suitable for use as electrode materials. To improve the properties of the electrochemical element, it is desirable to include a sulfide-based solid electrolyte, and it is even more desirable to include an argyrodite-type sulfide-based solid electrolyte.

[0075] Furthermore, the average particle size of the solid electrolyte is preferably 0.1 μm or larger, and more preferably 0.2 μm or larger, from the viewpoint of reducing grain boundary resistance. On the other hand, from the viewpoint of forming a sufficient contact interface between the active material and the solid electrolyte, it is preferably 10 μm or smaller, and more preferably 5 μm or smaller.

[0076] When a solid electrolyte is included in the electrode mixture, its content (including the amount of solid electrolyte if the electrode material used in the electrode mixture contains a solid electrolyte) is preferably 4 to 80% by mass.

[0077] Furthermore, the content of the active material in the electrode mixture (the amount of active material used in the electrode mixture or the amount of active material derived from the electrode material) is preferably 20 to 95% by mass.

[0078] When an electrode has a current collector, the following can be used for the current collector: When the electrode is the positive electrode of an electrochemical element, metal foils such as aluminum, nickel, or stainless steel, perforated metal, mesh, expanded metal, foamed metal; carbon sheets; etc. can be used for the current collector. When the electrode is the negative electrode of an electrochemical element, copper, nickel, or aluminum foils, perforated metal, mesh, expanded metal, foamed metal; carbon sheets; etc. can be used for the current collector.

[0079] The molded electrode mixture can be formed, for example, by compressing an electrode mixture prepared by mixing the active material or electrode material of the present invention with a conductive additive, binder, solid electrolyte, etc., which are added as needed, by pressure molding or the like.

[0080] In the case of electrodes having a current collector, they can be manufactured by bonding a molded electrode mixture formed by the method described above to the current collector by pressing or other means.

[0081] Alternatively, an electrode mixture containing an electrode mixture may be prepared by mixing the electrode mixture with a solvent, and this mixture may be applied to a substrate such as a current collector or a solid electrolyte layer (in the case of forming an all-solid-state battery) that faces the electrodes. After drying, a press treatment may be performed to form a molded body of the electrode mixture.

[0082] For the solvent in the electrode mixture-containing composition, organic solvents such as water or N-methyl-2-pyrrolidone (NMP) can be used. When the electrode mixture-containing composition also contains a solid electrolyte, it is preferable to select a solvent that does not easily degrade the solid electrolyte. In particular, since sulfide-based and hydride-based solid electrolytes undergo chemical reactions with even small amounts of water, it is preferable to use non-polar aprotic solvents such as hydrocarbon solvents like hexane, heptane, octane, nonane, decane, decalin, toluene, xylene, messtyrene, and tetralin. It is even more preferable to use an ultra-dehydrated solvent with a water content of 0.001% by mass (10 ppm) or less. Furthermore, fluorine-based solvents such as "Bartrell®" from Mitsui DuPont Fluorochemicals, "Zeolora®" from Nippon Zeon Corporation, and "Novec®" from Sumitomo 3M, as well as non-aqueous organic solvents such as dichloromethane, diethyl ether, and anisole, can also be used.

[0083] The thickness of the molded electrode mixture (in the case of an electrode with a current collector, the thickness of the molded electrode mixture per side of the current collector; the same applies hereinafter) is usually 50 μm or more, but from the viewpoint of increasing the capacitance of the electrochemical element, it is preferable to have a thickness of 200 μm or more. Generally, the load characteristics of an electrochemical element can be easily improved by making the positive or negative electrode thinner, but according to the present invention, it is possible to improve the load characteristics even when the molded electrode mixture is thick, such as 200 μm or more. Therefore, in the present invention, the effect becomes more pronounced when the thickness of the molded electrode mixture is, for example, 200 μm or more. Furthermore, the thickness of the molded electrode mixture is usually 3000 μm or less.

[0084] In the case of electrodes for electrochemical elements manufactured by forming an electrode mixture layer on a current collector using an electrode mixture-containing composition that contains a solvent, the thickness of the electrode mixture layer is preferably 50 to 1000 μm.

[0085] <Electrochemical elements> The electrochemical element of the present invention has a positive electrode and a negative electrode, and either the positive electrode or the negative electrode may be an electrode for the electrochemical element of the present invention. There are no particular restrictions on other configurations and structures, and various configurations and structures used in conventionally known electrochemical elements such as non-aqueous electrolyte secondary batteries can be applied.

[0086] The electrochemical elements of the present invention include non-aqueous electrolyte secondary batteries such as non-aqueous electrolyte secondary batteries having a separator and a non-aqueous electrolyte interposed between a positive electrode and a negative electrode, and all-solid-state secondary batteries having a solid electrolyte layer between a positive electrode and a negative electrode; supercapacitors; and other electrochemical elements having a non-aqueous electrolyte. However, the following will describe in detail a non-aqueous electrolyte secondary battery, which is a typical embodiment of the electrochemical elements of the present invention.

[0087] Figure 1 shows a schematic cross-sectional view of a non-aqueous electrolyte secondary battery, which is an example of an electrochemical element of the present invention. The non-aqueous electrolyte secondary battery 1 shown in Figure 1 has an outer casing formed by an outer casing 40, a sealing casing 50, and a resin gasket 60 interposed between them, and contains a positive electrode 10, a negative electrode 20, a separator (a solid electrolyte layer if the non-aqueous electrolyte secondary battery is an all-solid-state secondary battery) 30 interposed between the positive electrode 10 and the negative electrode 20, and a non-aqueous electrolyte (if the non-aqueous electrolyte secondary battery is a non-aqueous electrolyte secondary battery).

[0088] The sealing can 50 is fitted into the opening of the outer can 40 via a gasket 60, and the open end of the outer can 40 is tightened inward, causing the gasket 60 to come into contact with the sealing can 50, thereby sealing the opening of the outer can 40 and creating a sealed structure inside the battery.

[0089] Stainless steel can be used for the outer casing and sealing can. Polypropylene and nylon can be used as gasket materials, and if heat resistance is required due to the battery's application, heat-resistant resins with melting points exceeding 240°C, such as fluororesins like tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), can also be used. Furthermore, if the battery is used in an application requiring heat resistance, a glass hermetic seal can be used for sealing.

[0090] Furthermore, Figures 2 and 3 schematically represent other examples of non-aqueous electrolyte secondary batteries, which are examples of electrochemical elements of the present invention. Figure 2 is a plan view of a non-aqueous electrolyte secondary battery, and Figure 3 is a cross-sectional view taken along line II of Figure 2.

[0091] The non-aqueous electrolyte secondary battery 100 shown in Figures 2 and 3 houses an electrode body 200 within a laminate film casing 500 made of two metal laminate films. The laminate film casing 500 is sealed by heat-sealing the upper and lower metal laminate films at its outer periphery.

[0092] In the case of the non-aqueous electrolyte secondary battery 100 being an all-solid-state secondary battery, the electrode body 200 is constructed by stacking a positive electrode, a negative electrode, and a solid electrolyte layer interposed between them. On the other hand, in the case of the non-aqueous electrolyte secondary battery 100 being a non-aqueous electrolyte secondary battery other than an all-solid-state secondary battery, the electrode body 200 is constructed by stacking a positive electrode, a negative electrode, and a separator interposed between them, and the non-aqueous electrolyte is sealed inside the laminate film outer casing 500 together with this electrode body 200.

[0093] Note that in Figure 3, in order to avoid making the drawing complicated, the individual layers constituting the laminate film outer casing 500 and the individual components (positive electrode, negative electrode, etc.) forming the electrode body 200 are not shown separately.

[0094] The positive electrode of the electrode body 200 is connected to the positive electrode external terminal 300 inside the battery 100, and although not shown in the diagram, the negative electrode of the electrode body 200 is also connected to the negative electrode external terminal 400 inside the battery 100. The positive electrode external terminal 300 and the negative electrode external terminal 400 have one end extended to the outside of the laminate film casing 500 so that they can be connected to external devices.

[0095] Furthermore, if the non-aqueous electrolyte secondary battery is an all-solid-state secondary battery, the electrode of the present invention uses an electrode mixture that contains a solid electrolyte. On the other hand, if the non-aqueous electrolyte secondary battery is a non-aqueous electrolyte secondary battery, the electrode mixture according to the present invention does not need to contain a solid electrolyte.

[0096] Furthermore, when manufacturing a non-aqueous electrolyte secondary battery using an electrode containing the active material of the present invention as the positive electrode and a negative electrode that does not contain Li (Li ions) involved in the charging and discharging of the battery, it is necessary to introduce Li (Li ions) involved in the charging and discharging of the battery into the active material of the electrode of the present invention. In this case, for example, the active material of the present invention can be pre-doped with Li ions by a standard method (external pre-doping), or, if the non-aqueous electrolyte secondary battery has a non-aqueous electrolyte, a Li source (metallic Li foil, Li alloy foil, etc.) can be placed in a location that can come into contact with the non-aqueous electrolyte inside the battery, thereby doping the active material of the electrode of the present invention with Li ions within the battery (in-system pre-doping). In the case of the above-mentioned in-system pre-doping, for example, a pre-doping electrode can be used in which a Li source is attached to the surface of a current collector and is electrically connected to the negative electrode.

[0097] <Negative electrode relating to a non-aqueous electrolyte secondary battery using the electrode of the present invention as the positive electrode> When the positive electrode of a non-aqueous electrolyte secondary battery is the electrode of the present invention, the negative electrode may consist only of a molded body of a negative electrode mixture containing a negative electrode active material and a conductive additive, or it may have a structure in which a layer made of a molded body of the negative electrode mixture (negative electrode mixture layer) is formed on a current collector.

[0098] As the negative electrode active material, one or more carbon-based materials capable of intercalating and releasing lithium can be used, such as graphite, pyrolysis carbons, cokes, glassy carbons, calcined organic polymer compounds, mesophase carbon microbeads (MCMBs), and carbon fibers. In addition, elements such as Al, Si, Sn, Ge, Bi, Sb, In, Zn, and P, as well as their compounds and alloys; compounds that can be charged and discharged at low voltages close to lithium metal, such as lithium-containing nitrides or lithium-containing sulfides; and lithium metal itself can also be used as negative electrode active materials.

[0099] The content of the negative electrode active material in the negative electrode mixture is preferably 15 to 100% by mass.

[0100] For the conductive additive in the negative electrode, the same as those previously exemplified as usable in the electrode of the present invention can be used. Preferably, the content of the conductive additive in the negative electrode mixture is 0.1 to 15% by mass.

[0101] When the non-aqueous electrolyte secondary battery using the electrode of the present invention as the positive electrode is an all-solid-state secondary battery, and the negative electrode active material is in particulate form, the negative electrode mixture can contain a solid electrolyte.

[0102] For the negative electrode solid electrolyte, one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as materials that can be used in the electrode material of the present invention can be used. To improve battery characteristics, it is desirable to include a sulfide-based solid electrolyte, and it is even more desirable to include an argyrodite-type sulfide-based solid electrolyte.

[0103] The solid electrolyte content in the negative electrode mixture is preferably 4 to 90% by mass.

[0104] The negative electrode mixture may contain a binder, but it may not be necessary to include one if good moldability can be ensured without using a binder, such as in the case of a negative electrode containing a sulfide-based solid electrolyte, where the powder of the negative electrode mixture is placed in a molding die and compacted. The binder can be the same as those previously exemplified as those that can be used in the electrodes of the present invention.

[0105] In the negative electrode mixture, if a binder is required, its content is preferably 15% by mass or less, and more preferably 0.5% by mass or more. On the other hand, in the negative electrode mixture, if a binder is not required from the viewpoint of moldability, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0% by mass (i.e., no binder is included).

[0106] When a current collector is used for the negative electrode, the same current collector as previously exemplified as one that can be used when the electrode of the present invention is the negative electrode can be used.

[0107] A molded negative electrode mixture can be formed, for example, by compressing a negative electrode mixture prepared by mixing a negative electrode active material with conductive additives, binders, solid electrolytes, etc., as needed, using pressure molding or similar methods. In the case of a negative electrode consisting only of a molded negative electrode mixture, it can be manufactured by the method described above.

[0108] In the case of a negative electrode having a current collector, it can be manufactured by bonding a molded negative electrode mixture formed by the method described above to the current collector by pressing or other means.

[0109] Furthermore, in the case of a negative electrode having a current collector, it can also be manufactured by applying a negative electrode mixture-containing composition (paste, slurry, etc.), obtained by dispersing the aforementioned negative electrode mixture in a solvent, to the current collector, drying it, and then, if necessary, applying pressure molding such as calendering to form a molded negative electrode mixture (negative electrode mixture layer) on the surface of the current collector.

[0110] The solvent for the negative electrode mixture-containing composition can be water or an organic solvent such as NMP. When the negative electrode mixture-containing composition also contains a solid electrolyte, it is desirable to select a solvent that does not easily degrade the solid electrolyte, and it is preferable to use the same solvents as those previously exemplified for electrode mixture-containing compositions containing solid electrolytes.

[0111] The thickness of the molded negative electrode mixture (in the case of a negative electrode with a current collector, the thickness of the molded positive electrode mixture per side of the current collector; the same applies hereinafter) is usually 50 μm or more, but from the viewpoint of increasing the battery capacity, it is preferable to have a thickness of 200 μm or more. In addition, the thickness of the molded negative electrode mixture is usually 2000 μm or less.

[0112] In the case of a negative electrode manufactured by forming a negative electrode mixture layer on a current collector using a negative electrode mixture-containing composition that contains a solvent, the thickness of the negative electrode mixture layer is preferably 50 to 1000 μm.

[0113] <Positive electrode related to a non-aqueous electrolyte secondary battery using the electrode of the present invention as the negative electrode> When the negative electrode in a non-aqueous electrolyte secondary battery is the electrode of the present invention, the positive electrode may consist only of a molded body of a positive electrode mixture containing a positive electrode active material and a conductive additive, or it may have a structure in which a layer made of a molded body of a positive electrode mixture (positive electrode mixture layer) is formed on a current collector.

[0114] The positive electrode active material is not particularly limited as long as it is a positive electrode active material that has been used in conventional non-aqueous electrolyte secondary batteries, that is, an active material that can absorb and release Li ions. A specific example of a positive electrode active material is LiM r Mn 2-r O4 (where M is at least one element selected from the group consisting of Li, Na, K, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Zr, Fe, Co, Ni, Cu, Zn, Al, Sn, Sb, In, Nb, Ta, Mo, W, Y, Ru, and Rh, and 0 ≤ r ≤ 1), a spinel-type lithium manganese composite oxide, Li r Mn (1-s-r) Ni s Mt O (2-u) F v (wherein M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr and W, 0.8≦r≦1.2, 0<s<0.5, 0≦t≦0.5, u+v<1, -0.1≦u≦0.2, 0≦v≦0.1), a layered compound represented by the formula LiCo 1-r M r O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, V, Cr, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≦r≦0.5), a lithium cobalt composite oxide represented by the formula LiNi 1-r M r O2 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, 0≦r≦0.5), a lithium nickel composite oxide represented by the formula Li 1+s M 1-r N r PO4F s (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≦r≦0.5, 0≦s≦1), an olivine-type composite oxide represented by the formula Li2M 1-r N r P2O7 (wherein M is at least one element selected from the group consisting of Fe, Mn and Co, N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, V and Ba, 0≦r≦0.5), a pyrophosphate compound, and the like. Only one of these may be used, or two or more thereof may be used in combination.

[0115] In the case of a non-aqueous electrolyte secondary battery that is an all-solid-state secondary battery, the average particle size of the positive electrode active material is preferably 0.1 μm or more, more preferably 0.5 μm or more, preferably 25 μm or less, and more preferably 10 μm or less, from the viewpoint of reducing side reactions that cause degradation of the battery capacity and increasing the density of the electrode. The positive electrode active material may be primary particles or secondary particles formed by aggregating primary particles. Using a positive electrode active material with an average particle size within the above range allows for a larger interface with the solid electrolyte contained in the positive electrode, thereby improving the load characteristics of the battery.

[0116] In the case of a non-aqueous electrolyte secondary battery that is an all-solid-state secondary battery, it is preferable that the positive electrode active material has a reaction-inhibiting layer on its surface to suppress the reaction with the solid electrolyte contained in the positive electrode.

[0117] In a molded positive electrode mixture, direct contact between the positive electrode active material and the solid electrolyte can cause the solid electrolyte to oxidize, forming a resistance layer and potentially reducing the ionic conductivity within the molded body. By providing a reaction-inhibiting layer on the surface of the positive electrode active material to suppress its reaction with the solid electrolyte, direct contact between the positive electrode active material and the solid electrolyte can be prevented, thereby suppressing the reduction in ionic conductivity within the molded body due to oxidation of the solid electrolyte.

[0118] The reaction suppression layer may be composed of a material that has ionic conductivity and can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of materials that can constitute the reaction suppression layer include oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti, Zr, Ta, and W, more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, Li2WO4, etc. The reaction suppression layer may contain only one of these oxides, or it may contain two or more, and furthermore, multiple of these oxides may form a composite compound. Among these oxides, it is preferable to use an Nb-containing oxide, and more preferable to use LiNbO3.

[0119] The reaction-suppressing layer is preferably present on the surface in an amount of 0.1 to 2.0 parts by mass per 100 parts by mass of positive electrode active material. Within this range, the reaction between the positive electrode active material and the solid electrolyte can be effectively suppressed.

[0120] Methods for forming a reaction-inhibiting layer on the surface of the positive electrode active material include the sol-gel method, mechanofusion method, CVD method, PVD method, and ALD method.

[0121] The content of the positive electrode active material in the positive electrode mixture is preferably 20 to 95% by mass.

[0122] As the conductive additive for the positive electrode, the same as those previously exemplified as usable in the electrode of the present invention can be used. The content of the conductive additive in the positive electrode mixture is preferably 0.1 to 15% by mass.

[0123] When a non-aqueous electrolyte secondary battery is an all-solid-state secondary battery, the positive electrode mixture contains a solid electrolyte.

[0124] For the positive electrode solid electrolyte, one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as usable in the electrode material of the present invention can be used. To improve battery characteristics, it is desirable to include a sulfide-based solid electrolyte, and it is even more desirable to include an argyrodite-type sulfide-based solid electrolyte.

[0125] The solid electrolyte content in the positive electrode mixture is preferably 4 to 80% by mass.

[0126] A binder may be included in the positive electrode mixture, but it may not be included if good moldability can be ensured without using a binder, such as in the case of a positive electrode containing a sulfide-based solid electrolyte, where the powder of the positive electrode mixture is placed in a molding die and compacted. The binder can be the same as those previously exemplified as usable in the electrodes of the present invention.

[0127] In the positive electrode mixture, if a binder is required, its content is preferably 15% by mass or less, and more preferably 0.5% by mass or more. On the other hand, in the positive electrode mixture, if a binder is not required from the viewpoint of moldability, its content is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0% by mass (i.e., no binder is included).

[0128] When a current collector is used for the positive electrode, the same current collector as previously exemplified as one that can be used when the electrode of the present invention is the positive electrode can be used.

[0129] A molded positive electrode mixture can be formed, for example, by compressing a positive electrode mixture prepared by mixing a positive electrode active material and a conductive additive with a binder and solid electrolyte, which may be added as needed, using pressure molding or the like. A positive electrode consisting solely of a molded positive electrode mixture can be manufactured by the method described above.

[0130] In the case of a positive electrode having a current collector, it can be manufactured by bonding the positive electrode mixture formed by the method described above to the current collector by pressing or other means.

[0131] Furthermore, in the case of a positive electrode having a current collector, it can also be manufactured by applying a positive electrode mixture-containing composition (paste, slurry, etc.), obtained by dispersing the positive electrode mixture in a solvent, to the current collector, drying it, and then, if necessary, applying pressure molding such as calendering to form a molded positive electrode mixture (positive electrode mixture layer) on the surface of the current collector.

[0132] For the solvent in the positive electrode mixture-containing composition, organic solvents such as NMP can be used. When the positive electrode mixture-containing composition also contains a solid electrolyte, it is desirable to select a solvent that does not easily degrade the solid electrolyte, and it is preferable to use the same solvents as those previously exemplified for electrode mixture-containing compositions containing solid electrolytes.

[0133] The thickness of the molded positive electrode mixture (in the case of a positive electrode with a current collector, the thickness of the molded positive electrode mixture per side of the current collector; the same applies hereinafter) is usually 50 μm or more, but from the viewpoint of increasing the battery capacity, it is preferable to have a thickness of 200 μm or more. In addition, the thickness of the molded positive electrode mixture is usually 2000 μm or less.

[0134] In the case of a positive electrode manufactured by forming a positive electrode mixture layer on a current collector using a positive electrode mixture-containing composition that contains a solvent, the thickness of the positive electrode mixture layer is preferably 50 to 1000 μm.

[0135] (solid electrolyte layer) When a non-aqueous electrolyte secondary battery is an all-solid-state secondary battery, the solid electrolyte in the solid electrolyte layer interposed between the positive electrode and the negative electrode can be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes exemplified above as materials that can be used in the electrode materials of the present invention. However, in order to improve the battery characteristics, it is desirable to include a sulfide-based solid electrolyte, and it is even more desirable to include an argyrodite-type sulfide-based solid electrolyte. Furthermore, it is even more desirable to include a sulfide-based solid electrolyte in all of the positive electrode, negative electrode, and solid electrolyte layer, and it is even more desirable to include an argyrodite-type sulfide-based solid electrolyte.

[0136] The solid electrolyte layer may have a porous material, such as a resin nonwoven fabric, as a support.

[0137] The solid electrolyte layer can be formed by methods such as compressing a solid electrolyte by pressure molding; or by applying a solid electrolyte layer-forming composition, prepared by dispersing a solid electrolyte in a solvent, onto a substrate, positive electrode, or negative electrode, drying it, and then performing pressure molding such as a press treatment as needed.

[0138] When selecting a solvent for a composition that forms a solid electrolyte layer, it is desirable to choose one that does not easily degrade the solid electrolyte, and it is preferable to use the same solvents as those previously exemplified for an electrode mixture containing a solid electrolyte.

[0139] The thickness of the solid electrolyte layer is preferably 10 to 500 μm.

[0140] (Separator) When a non-aqueous electrolyte secondary battery is a battery other than an all-solid-state secondary battery, the separator interposed between the positive and negative electrodes should be one that has sufficient strength and can hold a large amount of non-aqueous electrolyte. From this viewpoint, microporous films or nonwoven fabrics containing polyethylene, polypropylene, or ethylene-propylene copolymer, with a thickness of 10 to 50 μm and an aperture ratio of 30 to 70%, are preferred.

[0141] (Non-aqueous electrolytes) When a non-aqueous electrolyte secondary battery is a battery other than an all-solid-state secondary battery, a non-aqueous liquid electrolyte (hereinafter referred to as "non-aqueous electrolyte") is usually used as the non-aqueous electrolyte. The non-aqueous electrolyte is prepared by dissolving an electrolyte salt such as a lithium salt in an organic solvent. The organic solvent is not particularly limited, but examples include chain-like esters such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate; cyclic esters with high dielectric constants such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; and mixed solvents of chain-like esters and cyclic esters. Mixed solvents of chain-like esters and cyclic esters are particularly suitable.

[0142] Examples of electrolyte salts to be dissolved in organic solvents when preparing non-aqueous electrolytes include LiPF6, LiBF4, LiAsF6, LiSbF6, LiCF3SO3, LiC4F9SO3, LiCF3CO2, Li2C2F4(SO3)2, and LiC n F 2n+1SO3 (n≧2), LiN(RfSO2)(Rf'SO2), LiC(RfSO2)3, LiN(RfOSO2)2 (where Rf and Rf' are fluoroalkyl groups), etc., can be used individually or in combination of two or more. The concentration of the electrolyte salt in the non-aqueous electrolyte is not particularly limited, but is preferably 0.3 mol / l or higher, more preferably 0.4 mol / l or higher, preferably 1.7 mol / l or lower, and more preferably 1.5 mol / l or lower.

[0143] In a non-aqueous electrolyte secondary battery, in addition to the non-aqueous electrolyte solution, a gel-like electrolyte can also be used, which is obtained by gelling the non-aqueous electrolyte solution with a gelling agent such as a polymer.

[0144] (electrode body) The positive and negative electrodes can be used in batteries in the form of a laminated electrode body, which is formed by stacking solid electrolyte layers or separators, or in the form of a wound electrode body, which is formed by winding this laminated electrode body.

[0145] Furthermore, when forming an electrode body having a solid electrolyte layer, it is preferable to pressure-molde the positive electrode, negative electrode, and solid electrolyte layer in a stacked state, from the viewpoint of increasing the mechanical strength of the electrode body.

[0146] (Battery type) Non-aqueous electrolyte secondary batteries can take the form of an outer casing consisting of an outer casing, a sealing casing, and a gasket, as shown in Figure 1, that is, the form generally referred to as a coin-type battery or button-type battery, or an outer casing consisting of a resin film or a metal-resin laminate film, as shown in Figures 2 and 3. In addition, they may also have an outer casing that is made of metal, has a bottomed cylindrical (cylindrical or rectangular) outer casing, and a sealing structure that seals its opening.

[0147] (Db / Da after battery charging and discharging) By charging and discharging a non-aqueous electrolyte secondary battery, the Db / Da value of the active material (the active material of the present invention) in the battery increases. [Examples]

[0148] Hereinafter, the present invention will be described in detail based on Examples. However, the following Examples are not intended to limit the present invention.

[0149] Example 1 <Preparation of Positive Electrode> 0.86 g of lithium and 38.7 g of pentaethoxyniobium were mixed in 394 g of dehydrated ethanol to prepare a coating liquid for forming a reaction suppression layer. Next, using a coating apparatus with a tumbling fluidized bed, 1000 g of positive electrode active material (LiNi 0.5 Mn 1.5 O4) was coated with the aforementioned coating liquid for forming a reaction suppression layer at a rate of 2 g per minute. The obtained powder was heat-treated at 350°C to obtain a positive electrode material in which a reaction suppression layer composed of 2 parts by mass of LiNbO3 was formed on the surface relative to 100 parts by mass of the positive electrode active material.

[0150] The aforementioned positive electrode material, vapor-grown carbon fiber (conductive aid), and Li 5.8 PS 4.6 Cl 1.6 (sulfide-based solid electrolyte) were mixed to prepare a positive electrode mixture. The mass ratio of the positive electrode material, the conductive aid, and the sulfide-based solid electrolyte was 66:4:30. 102 mg of this positive electrode mixture was charged into a powder molding die with a diameter of 7.5 mm, and molding was performed using a press machine at 1000 kgf / cm 2 to fabricate a positive electrode composed of a cylindrical positive electrode mixture molded body.

[0151] <Formation of Solid Electrolyte Layer> 16 mg of a sulfide-based solid electrolyte (Li 5.4 PS 4.2 Cl 0.8 Br 0.8 ) was placed on the positive electrode inside the aforementioned powder molding die, and molding was performed using a press machine at 1000 kgf / cm 2 to form a solid electrolyte layer on the positive electrode mixture molded body.

[0152] <Preparation of Negative Electrode> Active materials were synthesized using a solid-phase reaction method with various metal oxide powders (all obtained from Kojunsei Kagaku Co., Ltd.) as starting materials. Nb2O5 (purity: >99.9%) and α-Al2O3 (purity: >99.99%) were weighed out at 96.73g and 3.37g respectively and mixed. The mixture of the starting materials was added to a 500ml zirconia container along with 70g of ethanol and 300g of 5mm diameter YSZ balls, and then milled in a planetary ball mill [Fritsch "planetary mill pulverisette 5" (product name)] for 2 The sample was mixed for 3 hours at 50 rpm, and the slurry obtained by separating zirconia balls from the mixed sample was dried to obtain a precursor powder of the negative electrode active material. The precursor powder was transferred to an alumina crucible, heated to 1000°C at a heating rate of 16°C / min under an atmospheric atmosphere, held for 4 hours to calcinate, and then allowed to cool naturally to room temperature. The obtained powder was crushed in a mortar for 5 minutes and passed through a sieve with a mesh size of 150 μm to obtain the crude product of the active material. 4 g of the crude product of the active material was added to a 12.5 ml zirconia container together with 4 g of ethanol and 30 g of 5 mm diameter YSZ balls, and crushed in the planetary ball mill at 250 rpm for 3 hours. The obtained slurry was dried under reduced pressure at 60°C overnight to obtain the negative electrode active material, AlNb 11 O 29 I obtained it.

[0153] The obtained powder XRD pattern of the negative electrode active material was measured, confirming that the negative electrode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the negative electrode active material had a Da of 13.5 nm, a Db of 82.5 nm, a Db / Da [D(020) / D(200)] of 6.11, and an average particle size of 1.144 μm.

[0154] The aforementioned negative electrode active material and a sulfide-based solid electrolyte (Li 5.4 PS 4.2 Cl 0.8 Br 0.8The anode mixture was prepared by mixing the anode mixture with graphene (a conductive additive) in a mass ratio of 60:33:7 and kneading thoroughly. Next, 67 mg of the anode mixture was placed on top of the solid electrolyte layer in the powder molding die and pressed using a press machine at 10,000 kgf / cm². 2 A laminated electrode body was fabricated by forming a negative electrode made of a negative electrode mixture molded body on the solid electrolyte layer by molding under pressure, thereby stacking the positive electrode, solid electrolyte layer, and negative electrode.

[0155] <Assembly of all-solid-state batteries> Flexible graphite sheet "PERMA-FOIL" (product name) manufactured by Toyo Tanso Co., Ltd. (thickness: 0.1 mm, apparent density: 1.1 g / cm³) 3 Two pieces of graphite were prepared, each punched out to the same size as the laminated electrode body. One of these pieces was placed on the inner bottom surface of a stainless steel sealing can fitted with a polypropylene annular gasket. Next, the laminated electrode body was placed on top of the graphite sheet with the negative electrode facing the graphite sheet, and the other graphite sheet was placed on top of that. After covering it with a stainless steel outer can, the open end of the outer can was crimped inward to seal it, thereby creating a flat, all-solid-state secondary battery with a diameter of approximately 9 mm, in which the graphite sheet was placed between the inner bottom surface of the sealing can and the laminated electrode body, and between the inner bottom surface of the outer can and the laminated electrode body.

[0156] Example 2 Except for using a mixture of 96.72g, 2.34g, and 1.04g of Nb2O5 (purity: >99.9%), α-Al2O3 (purity: >99.99%), and CuO (purity: >99.99%) as the starting material, the negative electrode active material was prepared in the same manner as in Example 1. Cu 0.2 Al 0.7 Nb 11.1 O 29 The anode active material was synthesized. The powder XRD pattern of the obtained anode active material was measured, and it was confirmed that the anode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the anode active material had a Da of 43.7 nm, a Db of 96.7 nm, and a Db / Da [D(020) / D(200)] of 2.21.

[0157] Then, the negative electrode active material is the aforementioned Cu 0.2 Al 0.7 Nb 11.1 O 29 A flat-type all-solid-state secondary battery was fabricated in the same manner as in Example 1, except for the change made to [specific component].

[0158] Example 3 Except for the atmosphere during firing being a vacuum, the process was the same as in Example 1, using AlNb as the negative electrode active material. 11 O 29-δ AlNb was synthesized. 11 O 29-δ In this case, "δ" means that an oxygen vacancy is present, and charge compensation is Nb 5+ Nb inside 4+ It is done because of the presence of a mixture of these factors.

[0159] The obtained powder XRD pattern of the negative electrode active material was measured, confirming that the negative electrode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the negative electrode active material had a Da of 55.3 nm, a Db of 97.1 nm, a Db / Da [D(020) / D(200)] of 1.76, and an average particle size of 1.2507 μm.

[0160] Then, the negative electrode active material is the aforementioned AlNb 11 O 29-δ A flat-type all-solid-state secondary battery was fabricated in the same manner as in Example 1, except for the change made to [specific component].

[0161] Example 4 Except for the atmosphere during firing being a vacuum, the negative electrode active material Cu was prepared in the same manner as in Example 2. 0.2 Al 0.7 Nb 11.1 O 29-δ The following was synthesized. 0.2 Al 0.7 Nb 11.1 O 29-δ The "δ" in AlNb 11 O 29-δ This means that an oxygen vacancy has occurred, similar to the case in Nb. 5+Nb inside 4+ It is done because of the presence of a mixture of these factors.

[0162] The obtained powder XRD pattern of the negative electrode active material was measured, confirming that the negative electrode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the negative electrode active material had a Da of 20.7 nm, a Db of 90.3 nm, and a Db / Da [D(020) / D(200)] of 4.36.

[0163] Then, the negative electrode active material is the aforementioned Cu 0.2 Al 0.7 Nb 11.1 O 29-δ A flat-type all-solid-state secondary battery was fabricated in the same manner as in Example 1, except for the change made to [specific component].

[0164] Comparative Example 1 Except for setting the firing temperature to 1150°C, the process was the same as in Example 1, using AlNb as the negative electrode active material. 11 O 29 They were synthesized.

[0165] The obtained powder XRD pattern of the negative electrode active material was measured, confirming that the negative electrode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the negative electrode active material had a Da of 114 nm, a Db of 111 nm, a Db / Da [D(020) / D(200)] of 0.97, and an average particle size of 1.4518 μm.

[0166] Then, the negative electrode active material is the aforementioned AlNb 11 O 29 A flat-type all-solid-state secondary battery was fabricated in the same manner as in Example 1, except for the change made to [specific component].

[0167] Comparative Example 2 Except for setting the firing temperature to 1150°C, the negative electrode active material Cu was prepared in the same manner as in Example 2. 0.2 Al 0.7 Nb 11.1 O 29 They were synthesized.

[0168] The obtained anode active material powder XRD pattern was measured, confirming that the anode active material has a monoclinic crystal structure and belongs to the C2 / m space group. Furthermore, the anode active material had a Da of 109 nm, a Db of 142 nm, a Db / Da [D(020) / D(200)] of 1.30, and an average particle size of 1.6115 μm.

[0169] Then, the negative electrode active material is the aforementioned Cu 0.2 Al 0.7 Nb 11.1 O 29 A flat-type all-solid-state secondary battery was fabricated in the same manner as in Example 1, except for the change made to [specific component].

[0170] The load characteristics of each flat-type all-solid-state secondary battery in the examples and comparative examples were evaluated using the following method.

[0171] For each battery, constant current charging was performed at a current of 0.35mA until the voltage reached 4.2V, followed by constant voltage charging at 4.2V until the current value reached 0.025mA. Then, constant current discharge was performed at a current of 0.35mA until the voltage reached 1.5V. Next, for each battery, constant current charging was performed at a current of 1.5mA until the voltage reached 4.2V, followed by constant voltage charging at 4.2V until the current value reached 0.025mA.

[0172] Next, for each battery, a constant current discharge was performed at a current of 1.5 mA until the voltage reached 1.5 V, and the 1.5 mA discharge capacity was measured. Subsequently, the open-circuit voltage was measured for 1 hour, and then a constant current discharge was performed at a current of 0.1 mA until the voltage reached 1.5 V. The sum of the discharge capacity obtained from the 0.1 mA constant current discharge and the 1.5 mA discharge capacity was defined as the 0.1 mA discharge capacity.

[0173] The battery's charging characteristics (charging load characteristics) were evaluated by calculating the percentage of the total charging capacity obtained through constant-current charging and constant-voltage charging performed at the aforementioned 1.5mA current value. Furthermore, the battery's discharge characteristics (discharge load characteristics) were evaluated by calculating the value obtained by dividing the 1.5mA discharge capacity by the 0.1mA discharge capacity (capacity retention rate).

[0174] Furthermore, the negative electrode active material was extracted from each battery after the load characteristic evaluation, and Da and Db were measured using the method described above to determine Db / Da [D(020) / D(200)]. The Db / Da value of the negative electrode active material after charging and discharging was greater than the Db / Da value of the negative electrode active material before charging and discharging.

[0175] The compositional formula and Db / Da values ​​of the negative electrode active material are shown in Table 1, and the evaluation results are shown in Table 2. In Table 2, the charging and discharging characteristics are shown as relative values ​​with the results of Comparative Example 2 set to 100.

[0176] [Table 1]

[0177] [Table 2]

[0178] As shown in Tables 1 and 2, the flat-type all-solid-state secondary batteries of Examples 1 to 4, which used a negative electrode with a suitable Db / Da value of niobium composite oxide as the active material, showed good evaluation results for charging and discharging characteristics and possessed excellent load characteristics.

[0179] In contrast, the batteries in Comparative Examples 1 and 2, which used a negative electrode made of niobium composite oxide with an excessively small Db / Da ratio as the active material, exhibited poor charging and discharging characteristics, as well as inferior load characteristics.

[0180] Furthermore, Figure 4 shows graphs for each battery in Examples 1 and 3, and Comparative Examples 1 and 2, with the ratio of Da to average particle diameter ("Da / average particle diameter") in the niobium composite oxide used as the negative electrode active material plotted on the horizontal axis, and the charging and discharging characteristics (relative values ​​with the results of Comparative Example 2 set to 100) plotted on the vertical axis.

[0181] As shown in Figure 4, a certain correlation exists between the Da / average particle size of niobium composite oxide and the load characteristics (charging and discharging characteristics) of batteries using it as an active material. This result suggests that the smaller the size of the a-axis direction of the crystallites that traverse the active material particles as Li ions diffuse from the surface to the center, the better the load characteristics of the battery can be.

[0182] The present invention can also be implemented in forms other than those described herein, without departing from its spirit. The embodiments disclosed herein are examples, and the present invention is not limited to these embodiments. The scope of the present invention shall be interpreted in accordance with the claims attached, which take precedence over the description herein, and all modifications within the scope equivalent to the claims are included in the claims. [Industrial applicability]

[0183] The electrochemical element of the present invention can be applied to the same applications as conventional secondary batteries having non-aqueous electrolytes (non-aqueous electrolytes or gel-like electrolytes), all-solid-state secondary batteries, and supercapacitors. Furthermore, the electrode for the electrochemical element of the present invention can constitute the electrochemical element of the present invention, and the active material for the electrochemical element and the electrode material for the electrochemical element of the present invention can constitute the electrode for the electrochemical element of the present invention.

[0184] Furthermore, because the electrochemical element of the present invention has excellent load characteristics, it is suitable for applications where such characteristics are often required, such as power supply applications for industrial equipment and mobile devices (vehicles such as electric cars, hybrid cars, and electric motorcycles, ships, submarines, radio-controlled vehicles, flying objects such as rockets and satellites, drones, etc.). In addition, some mobile devices, such as hybrid cars, charge their batteries using regenerative energy. In this case, the charging current and voltage may be unstable, which can easily lead to the formation of Li dendrites in the battery, potentially causing battery degradation. However, since the electrochemical element of the present invention uses a niobium composite oxide as its active material, which is less prone to Li dendrite formation, it is possible to suppress degradation caused by Li dendrites even when charging using regenerative energy, and it can be suitably applied to mobile devices that perform such charging. [Explanation of Symbols]

[0185] 1. 100 Electrochemical elements (non-aqueous electrolyte secondary batteries) 10 positive electrode 20 negative electrode 30. Solid electrolyte layer or separator 40 outer cans 50 sealed cans 60 Gasket 200 Electrode body 300 Positive external terminal 400 Negative external terminal 500 Laminate film outer casing

Claims

1. An electrode active material for an electrochemical element, characterized in that it is a monoclinic niobium composite oxide, and when the crystallite size in the a-axis direction is Da and the crystallite size in the b-axis direction is Db, the ratio Db / Da is 1.5 or more.

2. The electrode active material for an electrochemical element according to claim 1, wherein the Db / Da ratio is 10 or less.

3. The electrode active material for an electrochemical element according to claim 1 or 2, wherein the Db / Da ratio is 1.7 or more.

4. The electrode active material for an electrochemical element according to any one of claims 1 to 3, wherein the Db / Da ratio is 3.0 or higher.

5. The aforementioned monoclinic niobium composite oxide is ReO 3 An electrode active material for an electrochemical element according to any one of claims 1 to 4, comprising a crystalline phase having a type crystal structure and a 3 × 4 × ∞ block structure in the crystallographic shear structure (C² / m, A² / m), or a crystalline phase belonging to a space group having a 3 × 3 × ∞ block structure (I² / m).

6. The electrode active material for an electrochemical element according to any one of claims 1 to 5, wherein the monoclinic niobium composite oxide is a composite oxide represented by the following general formula (1). M x Al 1-1.5x Nb 11+0.5x O 29-δ (1) [In the general formula (1) above, M is at least one element from Zn and Cu, and 0 ≤ x ≤ 0.4 and 0 ≤ δ ≤ 3.]

7. The electrode active material for an electrochemical element according to claim 6, wherein the monoclinic niobium composite oxide is represented by the general formula (1) and x = 0.

8. The electrochemical element electrode active material according to claim 6, wherein the monoclinic niobium composite oxide is represented by the general formula (1), and M is Cu, and 0 < x ≤ 0.

4.

9. The electrode active material for an electrochemical element according to any one of claims 1 to 8, wherein lithium ions are further inserted into the monoclinic niobium composite oxide.

10. The electrochemical element electrode active material according to any one of claims 1 to 9, wherein the monoclinic niobium composite oxide has a Da of 5 nm or more and a Db of 7.5 nm or more and a Db of 5000 nm or less.

11. An electrode material for an electrochemical element, characterized by containing an electrode active material for an electrochemical element according to any one of claims 1 to 10.

12. The electrode material for an electrochemical element according to claim 11, further comprising a solid electrolyte.

13. An electrode for an electrochemical element, characterized by containing an electrode active material for an electrochemical element according to any one of claims 1 to 10, or containing an electrode material for an electrochemical element according to claim 11 or 12.

14. An electrochemical element having a positive electrode and a negative electrode, wherein either the positive electrode or the negative electrode is an electrode for an electrochemical element as described in claim 13.

15. A mobile body characterized by having the electrochemical element described in claim 14.

Citation Information

Patent Citations

  • Active material for batteries, nonaqueous electrolyte battery and battery pack

    JP2016177972A

  • Active material, active material composite material, electrode, secondary battery, battery pack, and vehicle

    JP2019057371A